2008
DOI: 10.5713/ajas.2008.70604
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Green Tea By-product and Green Tea Probiotics on the Growth Performance, Meat Quality, and Immune Response of Finishing Pigs

Abstract: The objective of this experiment was to compare the effects of green tea by-product and green tea probiotics on the growth performance, meat quality and immune response of finishing pigs. A total of 72 crossbred "Landrace×Yorkshire" finishing pigs with an average of 76 kg body weight were assigned to 4 dietary treatments in a completely randomized design. Each treatment had 3 replications with 6 pigs per replication. The four dietary treatments were control, antibiotics (control diet with 0.003% chlortetracycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 28 publications
3
21
0
Order By: Relevance
“…The moisture and crude ash content of GM samples from goats fed GTB‐supplemented diet were statistically similar, which is consistent with the results of a study conducted by Ko et al. (). Conversely, Sarker et al.…”
Section: Discussionsupporting
confidence: 91%
“…The moisture and crude ash content of GM samples from goats fed GTB‐supplemented diet were statistically similar, which is consistent with the results of a study conducted by Ko et al. (). Conversely, Sarker et al.…”
Section: Discussionsupporting
confidence: 91%
“…Usage of probiotic in animal diet improved meat quality (Ko et al 2008, Zhou et al 2010. In the present experiment, we studied the effect of probiotic on broiler carcass composition to evaluate the quality of bird yields.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have already described the positive effects of tea, tea catechins, tea extract, and tea powder on animal performance and product quality [8][9][10][11][12][13][14][15] . However, many of these materials are too expensive to use in the livestock industry [16] . Green tea byproduct obtained through tea beverage production is reasonably cheap and effective, and has therefore been used as a feed supplement [16] .…”
Section: Introductionmentioning
confidence: 99%
“…However, many of these materials are too expensive to use in the livestock industry [16] . Green tea byproduct obtained through tea beverage production is reasonably cheap and effective, and has therefore been used as a feed supplement [16] . Yang et al [17] reported significantly lower TBA values in broiler meat of broilers that are fed diets containing 0.5% to 2.0% green tea by-product supplementation compared to those fed a diet containing antibiotics.…”
Section: Introductionmentioning
confidence: 99%